Monitoring Variation in Small Coastal Dolphin Populations: An Example from Darwin, Northern Territory, Australia - Brooks, Lyndon; Palmer, Carol; Griffiths, Anthony D.; Pollock, Kenneth H. (Frontiers in Marine Science, 2017)
Monitoring variation in populations of coastal dolphins presents a range of challenges. Many species occur at low local population levels, are cryptic and appear to range over larger areas than presumed. Here we present the results of a three and half year intensive monitoring study undertaken in Darwin Harbour and two neighboring sites (1086 km2). The study comprised multi-site robust design capture-recapture models that yielded estimates of abundance, apparent survival and temporary emigration on three species of coastal dolphins: Australian humpback (Sousa sahulensis), bottlenose (Tursiops sp.) and Australian snubfin (Orcaella heinsohni). Combining all three sites, abundance estimates varied between species. The Australian humpback was the most abundant species with a mean of 90, the bottlenose was stable at mean of 27 and the Australian snubfin varied widely from 19 to 70 with a mean of 41. Over time, Australian humpback abundance estimates showed a steady decline in Darwin Harbour but a population increase in the two neighboring sites was recorded, suggesting there were movements out of Darwin Harbour. However, the estimates of movement rates were not sufficiently sensitive to demonstrate this, due to the relatively small size of the local population and consequent low rates of observed movement. The multi-state robust design model offers the potential for more robust assessing of abundance estimates and population trends than other simpler designs. It is able to separate movements to and from a site from demographic changes on the site that otherwise might be confounded. The study highlights the substantial effort and time required to detect population trends for coastal dolphins is challenging, as is the need account for movement among sites when to populations are small and recapture rates are low.